Absence of disruptive TP53 mutations in high‐risk human papillomavirus‐driven neck squamous cell carcinoma of unknown primary. Issue 11 (15th August 2019) - Boscolo‐Rizzo, Paolo; Schroeder, Lea; Sacchetto, Valeria; Holzinger, Dana; Da Mosto, Maria Cristina; Tirelli, Giancarlo; Dal Cin, Elisa; Mantovani, Monica; Menegaldo, Anna; Del Mistro, Annarosa; Romeo, Salvatore; Dei Tos, Angelo Paolo; et al.
Abstract: Background: To enforce the evidence for causality between high‐risk human papillomavirus (hrHPV) infections and neck squamous cell carcinoma from unknown primary (NSCCUP) and provide biological basis for treatment de‐intensification, we searched for TP53 mutations in association with HPV status. Methods: TP53 mutations were searched for by amplification of exons 4 to 10. Results: Of the 70 NSCCUP, 27 (39%) harbored HPV infection. TP53 sequencing resulted in the identification of 19 patients harboring single mutations including 16 disruptive alterations (84%). The association of TP53 mutations and HPV could be evaluated in 48 NSCCUP including those with disruptive mutation in any exon (n = 16) and those without mutations but with complete sequence of exons 4 to 9 (n = 32): no disruptive mutations were found in the 17 HPV‐driven NSCCUP but in 16 of the 31 non‐HPV‐driven NSCCUP ( P = .0002). Conclusion: In a fraction of cases, NSCCUP is an HPV‐driven entity harboring wild‐type TP53 gene or nondisruptive TP53 mutations. HPV‐driven NSCCUP might benefit from treatment de‐intensification.